IMPORTANCE OF TEACHING SKILLS INTEGRATION IN EFL CALSSROOM - Numonjonova Charosxon Nodirbekovna (Лучшие интеллектуальные исследования, 2023)
The meaning of this article is that;teaching and learning are two basic processes underlying the activity of students and teachers nowadays. Learning process puts both parties toward each other , what it teaches , and what it takes, the teacher and the student. Today takes great importance to the training of students to teach themselves.By teaching skills integration helps teachers their lessons become more effective.